Pendaftaran Tanah Sebagai Tertib Administrasi Pertanahan dan Jaminan Kepastian Hukum Terhadap Pemegang Hak-hak Atas Tanah - Mezak, Meray Hendrik (Pelita Harapan University, 2006)
Law Registering as a prerequisite in land administration, will give benefit not just to state administration arrangement. But more than that, will give assurance to the law subject (person or corporate body) in its law certainty about rights for land, which will become a formal and strong evidence for the one who hold the certificate.